2003
DOI: 10.1207/s15402010bsm0104_5
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia as a Health Risk Factor

Abstract: This article reviewed insomnia epidemiological research, identifying areas where insomnia was a risk factor and isolating areas deserving of further investigation. Insomnia was consistently predictive of depression, anxiety disorders, other psychological disorders, alcohol abuse or dependence, drug abuse or dependence, and suicide, indicating insomnia is a risk factor for these difficulties. Additionally, insomnia was related to decreased immune functioning. The data were inconclusive regarding insomnia as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
206
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(235 citation statements)
references
References 34 publications
18
206
0
11
Order By: Relevance
“…In a review of epidemiological studies, Taylor et al (Taylor et al, 2003) found that insomnia predicted depression, anxiety, substance abuse or dependence, and suicide (Taylor et al, 2003). In fact, the correlation between insomnia and later development of depression within 1-3 years is particularly strong (Riemann & Voderholzer, 2003).…”
Section: Insomnia and Psychiatric Conditionsmentioning
confidence: 99%
“…In a review of epidemiological studies, Taylor et al (Taylor et al, 2003) found that insomnia predicted depression, anxiety, substance abuse or dependence, and suicide (Taylor et al, 2003). In fact, the correlation between insomnia and later development of depression within 1-3 years is particularly strong (Riemann & Voderholzer, 2003).…”
Section: Insomnia and Psychiatric Conditionsmentioning
confidence: 99%
“…This debilitating medical condition affects negatively the patients' daily performance. Among many other consequences, the patient suffers of cognitive, such as attention and memory, and emotional alterations [2]. They also become much more vulnerable to illnesses [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we will consider sleep quality as an important factor that may help explain the inconsistent links between CVC and depressive symptoms. Reduced sleep quality has emerged as an important risk factor in a variety of physical and mental health conditions including depression (see Imeri & Opp, 2009; Taylor, Lichstein, & Durrence, 2003), whereas high sleep quality may well have the potential to protect against elevated depressive symptoms in individuals with lower CVC.…”
mentioning
confidence: 99%